Photons vs. firewood: female (dis)empowerment by solar power in India - Stock, Ryan; Birkenholtz, Trevor (Gender, place and culture : a journal of feminist geography, 2020)
Renewable energy transitions are accelerating in the Global South. Yet many large-scale renewable energy infrastructures are developed on public lands with unknown impacts on commons access and usage. A prime example of this is the Gujarat Solar Park (GSP) in India, which is one of the world's largest solar photovoltaic facilities. The GSP is situated on 2,669 acres of previously common property, which has historically been used by female pastoralists for firewood collection. In this paper, we examine the following research questions: How do gender and caste power shape natural resource access in this region?; Does the Gujarat Solar Park exacerbate already gendered social-economic-political asymmetries? Our study utilizes a feminist political ecology framework to analyze the social dimensions of the GSP, drawing on recent work in this vein that uses a postcolonial and intersectional approach to examine the production of social difference through the spatial processes and political economy of solar energy generation. We find that the enclosure of public 'wastelands' to develop the Gujarat Solar Park has dispossessed resource-dependent women of access to firewood and grazing lands. This spatial dislocation is reinforcing asymmetrical social power relations at the village scale. Intersectional subject-positions are (re)produced vis-à-vis the exclusion of access to firewood in the land enclosed for the solar park. Affected women embody this dispossession through inter- and intra-village emotional geographies that cut across caste, class and gender boundaries.